Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1021/acs.jced.7b00273
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of (Solid + Liquid) Phase Equilibria in the Quaternary System NaBr + KBr + SrBr2 + H2O and Two Subsystems NaBr + SrBr2 + H2O and KBr + SrBr2 + H2O at T = 323 K

Abstract: The (solid + liquid) phase equilibria of the NaBr + KBr + SrBr2 + H2O quaternary system and two subsystems (NaBr + SrBr2 + H2O and KBr + SrBr2 + H2O) were studied at T = 323 K using the isothermal dissolution method. With the solubility values of each system, the stable phase diagrams of these systems were drawn. It shows that there is neither solid solution nor double salt in the diagrams. The three systems are all of the hydrate type I, and only one invariant point is found in the phase diagrams of the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Deng et al , researched the solubility relationships of the ternary systems NaBr + SrBr 2 + H 2 O, KBr + SrBr 2 + H 2 O, and LiBr + SrBr 2 + H 2 O at 288.15 K; at the same time, they used Pitzer and HW model to simulate the thermodynamic properties and predict the solubility data, and the predicted data agreed well with the measured solubilities. Our group has also studied a lot about phase equilibria of the systems containing magnesium bromide and strontium bromide, such as the ternary system CaBr 2 + MgBr 2 + H 2 O (348 K), the quinary system NaBr + KBr + MgBr 2 + SrBr 2 + H 2 O (323 K), and some of its subsystems (273, 298, 323, and 348 K); the results show that MgBr 2 can form double salts with KBr and CaBr 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al , researched the solubility relationships of the ternary systems NaBr + SrBr 2 + H 2 O, KBr + SrBr 2 + H 2 O, and LiBr + SrBr 2 + H 2 O at 288.15 K; at the same time, they used Pitzer and HW model to simulate the thermodynamic properties and predict the solubility data, and the predicted data agreed well with the measured solubilities. Our group has also studied a lot about phase equilibria of the systems containing magnesium bromide and strontium bromide, such as the ternary system CaBr 2 + MgBr 2 + H 2 O (348 K), the quinary system NaBr + KBr + MgBr 2 + SrBr 2 + H 2 O (323 K), and some of its subsystems (273, 298, 323, and 348 K); the results show that MgBr 2 can form double salts with KBr and CaBr 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, aiming at the utilization of strontium-rich underground brine in the Sichuan Basin, research on phase equilibrium of ternary systems NaCl–SrCl 2 –H 2 O and KCl–SrCl 2 –H 2 O at 348 K was carried out . Regarding the phase diagram of water–salt containing strontium bromide, the ternary subsystem mainly includes MgBr 2 –SrBr 2 –H 2 O at 298 and 323 K, and NaBr–SrBr 2 –H 2 O and KBr–SrBr 2 –H 2 O at 288, 308, and 323 K. The phase equilibrium in quaternary system NaBr–KBr–SrBr 2 –H 2 O at 348 K was investigated, which indicated that strontium bromide hexahydrate can be widely present at a temperature within 348 K …”
Section: Introductionmentioning
confidence: 99%
“…Solubility measurements containing calcium bromide have been conducted in ternary systems NaBr–CaBr 2 –H 2 O ( T = 348 K), KBr–CaBr 2 –H 2 O ( T = 348 K), NH 4 Br–CaBr 2 –H 2 O ( T = 298.15 and 323.15 K), and quaternary systems NaBr–KBr–CaBr 2 –H 2 O ( T = 298 K), NaBr–MgBr 2 –CaBr 2 –H 2 O ( T = 298 K), and KBr–MgBr 2 –CaBr 2 –H 2 O ( T = 298 and 323 K) . Solid–liquid equilibrium involving strontium bromide has been exhibited in ternary systems NaBr–SrBr 2 –H 2 O ( T = 288 and 323 K), KBr–SrBr 2 –H 2 O ( T = 288 and 323 K), , and MgBr 2 –SrBr 2 –H 2 O ( T = 298 and 323 K)…”
Section: Introductionmentioning
confidence: 99%